Evaluation of Information Quality on the Website of Mimika Regency Government - Alim Magal; Melkior N. N Sitokdana (Politeknik Pertanian Negeri Samarinda, 2021)
the current development of economic, political and technological globalization demands the implementation of an orientation of Good and Clean Government. To achieve this objective, the Indonesian government from central to regional level is required to implement an application of information and communication technology to improve effectiveness, efficiency, transparency and also accountability of public services. From the results of research and also from the results of audit of e-Government at local government level, apparently government’s websites on average are at the first level (preparation level), only a few of government’s websites have reached the second level (maturation level), while the third level (solidification level) and the fourth level (utilization level) have not been reached by government’s websites. This condition is influenced by the complexity of problems in Indonesia, such as the inequality of facilities and infrastructure, the low quality of human resources, high poverty rates, etc. Therefore, this research is conducted to evaluate the quality of the Mimika regency’s website. For a long time, the Mimika government has owned the website: http://www.mimikakab.go.id. Therefore, it will be very interesting to evaluate and recommend the result of evaluation to stakeholders so that steps can be taken for a tactical and strategic development.